ANALISIS EFISIENSI EKONOMI USAHATANI SEMANGKA NON BIJI DI KOTAMADYA PEKANBARU PROVINSI RIAU - Riski Akbar; Ermi Tety; Suardi Tarumun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research was aimed to analyze influence of production factors to without seed watermelon production at Pekanbaru City, analyzed economic efficiency of production factors who did by farmer in industrialist farmer at Pekanbaru City, to know the problems who were appear by farmer in without seed watermelon industrialist farmer at Pekanbaru City. This research was doing at Pekanbaru City which were located  in 4 district who were watermelon yield that were Tampan District, Tenayan Raya District, Rumbai District and Rumbai Pesisir District. This research was doing about 4 month, which was used survey method, sample taken by convenience random sampling method. The analysis used to know influence of production factors to without seed watermelon productions were Cobb-Douglas production function analysis, along with economic efficiency analysis. From this research gotten result production function of Cobb-Douglas showed that watermelon production were seed, animal fertilizer, NPK fertilizer, KCL fertilizer, Za fertilizer, pesticide, and labor. In an economic manner showed that efficiency value of seed and Za fertilizer not efficient, until need to using decrease in order to gotten efficiency by economic. Meanwhile KCL fertilizer still didn’t get efficiency in an economic manner with (NPM/Px > 1) until the use of KCL fertilizer still need to increase. At this research generally problem often farmer met in watermelon industrialist farmer was production tool procurement (fertilizer), and then unpredictable weather with high fall on rain. Key word: Efficiency, Production, Watermelon, Farmer